Croatiae auctores Latini - Jovanović, Neven, filolog (Array, 2012)
The text collection Croatiae auctores Latini (CroALa, first version 2009, http://www.ffzg.hr/klafil/croala/) publishes freely accessible, peer-reviewed editions of Latin texts, literary and otherwise, written by or about people of Croatian origin from the Middle Ages to the twentieth century. CroALa is of interest to scholars of Latin and Neo-Latin literature and language as well as of Croatian history and culture, but also to researchers from other disciplines and areas (history, art history, theology, even archaeology). The texts, which are edited, if not critically, then at least according to good scholarly practices, have been enhanced by additional information (e.g. bibliographic data, genre, metre, structural divisions) and by full-text search capabilities. In August 2012 CroALa comprised 276 documents by c. 131 authors, one special thematic sub-collection (the Laudationes urbium Dalmaticarum), as well as some secondary prosopographical and bibliographical data on Croatian Latin authors and texts. Research possibilities will be demonstrated by four examples of what we can find in the collection.